Hip Osteonecrosis Is Associated with Increased Plasma IL-33 Level - Jinhui Ma; Wanshou Guo; Zirong Li; Bailiang Wang; Shirui Li; Peng Wang (Mediators of Inflammation)
The recently discovered IL-33 as an IL-1 cytokine family member has been proved to be specifically released from osteonecrotic bones. We aimed to investigate the potential role of IL-33 in the development of osteonecrosis of femoral head (ONFH). Forty patients diagnosed with ONFH and forty age-, sex-, and body mass index- (BMI-) matched healthy subjects were included in this prospective study between March 2016 and September 2016. A commercially available ELISA kit was used to test the level of plasma IL-33. The IL-33 levels were compared among different ARCO stages, CJFH types, and etiology groups. Plasma IL-33 levels were significantly higher in the ONFH patients than that in the control subjects. The levels of IL-33 did not differ significantly among the ONFH patients with different ARCO stages. The IL-33 levels of patients with CJFH type L3 were significantly higher than that of patients with types L1 and L2. No significant differences were observed in IL-33 levels between steroid-induced, alcohol-induced, and idiopathic patients. Our findings seem to indicate that IL-33 effects may be detrimental during ONFH, which appeared to be associated with the prognosis of ONFH. The IL-33 deserves particular attention in the pathogenesis of ONFH.